Prevention and Control of Rabies in an Age of Global Travel: A Review of Travel‐ and Trade‐Associated Rabies Events – United States, 1986–2012. (22nd July 2013) - Lankau, E. W.; Cohen, N. J.; Jentes, E. S.; Adams, L. E.; Bell, T. R.; Blanton, J. D.; Buttke, D.; Galland, G. G.; Maxted, A. M.; Tack, D. M.; Waterman, S. H.; Rupprecht, C. E.; et al.
Summary Rabies prevention and control efforts have been successful in reducing or eliminating virus circulation regionally through vaccination of specific reservoir populations. A notable example of this success is the elimination of canine rabies virus variant from the United States and many other countries. However, increased international travel and trade can pose risks for rapid, long‐distance movements of ill or infected persons or animals. Such travel and trade can result in human exposures to rabies virus during travel or transit and could contribute to the re‐introduction of canine rabies variant or transmission of other viral variants among animal host populations. We present a review of travel‐ and trade‐associated rabies events that highlight international public health obligations and collaborative opportunities for rabies prevention and control in an age of global travel. Rabies is a fatal disease that warrants proactive coordination among international public health and travel industry partners (such as travel agents, tour companies and airlines) to protect human lives and to prevent the movement of viral variants among host populations.